2018
DOI: 10.1039/c7ee03364h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning mobility and stability of lithium ion conductors based on lattice dynamics

Abstract: Ionic conductivity and stability of Li-ion conductors are rationalized on the same footing using lattice-dynamics descriptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
241
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(312 citation statements)
references
References 66 publications
24
241
1
Order By: Relevance
“…In addition, the glass has a higher density of Li modes in the low-frequency region. Muy et al 79 have shown that a common feature of fast lithium conductors is low vibration frequencies. These lower frequencies are characteristic of larger thermal displacements, which correlate with a greater probability for migration.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the glass has a higher density of Li modes in the low-frequency region. Muy et al 79 have shown that a common feature of fast lithium conductors is low vibration frequencies. These lower frequencies are characteristic of larger thermal displacements, which correlate with a greater probability for migration.…”
Section: Resultsmentioning
confidence: 99%
“…A first example is the correlation between the diffusion coefficients or Arrhenius barriers of diffusion and the frequencies of specific optical phonons, first presented by Wakamura and Aniya [79][80][81] for halides. Evidence for such correlation has also been found in LISICONs, and in the family of olivines [82], and this descriptor constituted the backbone for a very recent screening for solid-state Li-ion conductors [83]. As a second example, the importance of accessible volume for diffusion [76,84] led to the development of the bond-valence method by Adams and Swenson [85], and several efforts [86,87] employed this inexpensive method for screening purposes.…”
Section: Introductionmentioning
confidence: 94%
“…Recent experimental studies associate a decrease in activation energy with a decrease in the pre-exponential factor and a lower ionic conductivity, suggesting that this factor can provide information about ionic conductivity. [42][43][44][45] Therefore, knowledge of the energy barriers alone is inadequate to support claims about high ionic conductivity within a material. AIMD simulations can provide more complete diffusional information in computational studies.…”
Section: Ab Initio Molecular Dynamics Simulationmentioning
confidence: 99%
“…However, other factors, such as the pre-exponential factor of the Arrhenius relation, are also critical to achieve a high ionic conductivity. The preexponential factor is related to many factors, including anion polarizability, lattice softness, mobile carrier concentration, and the ordering of the mobile-ion sublattice, [42][43][44][45] but design principles that consider these factors have not yet been developed. At the current stage, first-principles computation is required to identify the dopant and exact composition for a particular crystal structural framework to design a fast Li-ion conductor (Section 3.3).…”
Section: Design Principles For Fast Ion Conductorsmentioning
confidence: 99%